Como inserir mais sociobiodiversidade na alimentação escolar na Amazônia brasileira? - Tregidgo, Daniel; da Silva Maia, Juliana Kelly; Barros da Silva, Elenilma; Cardoso Lopes, Jessica; Larrosa Oler, Juliana Rodrigues; de Freitas Viana, Fernanda Maria; Rigo, Neide; Valsecchi, João; Lemos Lopes, Valdinei; de Menezes Neto, Elias Jacob; Medeiros Jacob, Michelle Cristine (Ethnobiology and Conservation, 2023)
Despite its rich sociobiodiversity, the Amazon faces significant challenges regarding food security. The Brazilian National School Feeding Programme (PNAE) emerges as a strategic opportunity to address the issue of food insecurity and to synergistically contribute to the conservation of biodiversity and the strengthening of local economic development. Although PNAE encourages the presence of regional foods and sociobiodiversity in school meals, the effective inclusion of these foods remains a challenge. In this policy brief, we summarize recommendations to promote the effective inclusion of sociobiodiversity in school meals in six strategies. We believe that the stakeholders directly involved in the PNAE decision-making can benefit from these recommendations, including public officials responsible for ensuring the human right to adequate food, as well as the institutions regulating the activities of nutritionists who serve as technical experts for the program.